2016
DOI: 10.1536/ihj.15-208
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Augmentation Index and Urinary Albumin Excretion With Benidipine in Hypertensive Patients With Chronic Kidney Disease

Abstract: SummaryAlthough calcium channel blockers (CCB) are expected to improve the augmentation index (AI) in CKD patients, the potential effect of benidipine on AI has been poorly studied.The present study aimed to compare the effect of benidipine and amlodipine in the treatment of CKD patients as measured through AI and urinary albumin excretion (UAE). Eligible patients with CKD were randomized to either the benidipine group or amlodipine group. Changes in UAE and AI were compared with target blood pressure level se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…5) However, sCr is an unreliable indicator during acute changes in kidney function, and alterations in sCr levels are not particularly sensitive or specific for small changes in the glomerular filtration rate (GFR). 6) In addition, sCr level could also be influenced by many factors such as age, gender, race, and intravascular volume. 6) Biomarkers such as kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) have been used for the early diagnosis of AKI, although with no definitive results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5) However, sCr is an unreliable indicator during acute changes in kidney function, and alterations in sCr levels are not particularly sensitive or specific for small changes in the glomerular filtration rate (GFR). 6) In addition, sCr level could also be influenced by many factors such as age, gender, race, and intravascular volume. 6) Biomarkers such as kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) have been used for the early diagnosis of AKI, although with no definitive results.…”
mentioning
confidence: 99%
“…6) In addition, sCr level could also be influenced by many factors such as age, gender, race, and intravascular volume. 6) Biomarkers such as kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) have been used for the early diagnosis of AKI, although with no definitive results. 7) Emerging evidence has revealed that the "aging suppressor" gene klotho deficiency is an early event in AKI, and a pathogenic factor that exacerbates acute kidney damage and contributes to long-term outcomes.…”
mentioning
confidence: 99%
“…Second, we have not considered whether other ARBs have similar effects and have not considered the effects of other types of antihypertensive, such as calcium channel blockers and diuretics. 30)…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of serum creatinine is not a reliable indicator during the period of acute kidney injury, and the variation of serum creatinine is not sensitive and specific enough for small changes in glomerular filtration rate. In addition, serum creatinine could be influenced by many factors, such as age, gender, race, intravascular volume and so on [16]. Urinary microalbumin is a sensitive index reflecting the permeability of glomerular capillaries, used for early evaluation of diabetic nephropathy and hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 99%